The thermoregulatory function of the human hand: How do palm and digit proportions affect heat loss?. Issue 4 (30th March 2018) - Payne, Stephanie; Macintosh, Alison; Stock, Jay
Abstract: Objectives: The current study assessed whether ecogeographical patterns seen in hand proportions correlate with heat loss directly. Using a brief severe cold immersion experiment on the hand, the influence of hand and digit dimensions on heat loss was evaluated. Materials and methods: A sample of 113 living individuals were tested. Two‐dimensional and three‐dimensional scanning techniques were used to assess hand and digit dimensions. Thermal imaging analysis was used to quantify heat loss during a 3‐min ice‐water immersion of the hands. Results: When body size was accounted for, hand width and digit length relative to total hand length were significant predictors of heat loss from the hand. Discussion: The current study provides empirical evidence to support the link between thermodynamic principles relating to surface area‐to‐volume ratio, and ecogeographical patterns associated with temperature.